Characterization of Carbon Felt Electrodes for Vanadium Redox Flow Batteries: Impact of Treatment Methods. Issue 11 (21st August 2018) - Eifert, L.; Banerjee, R.; Jusys, Z.; Zeis, R.
Abstract : In this study, we investigated the influence of thermal treatment, soaking in H2 SO4 and electrochemical ageing on commercially available carbon felt materials from SGL carbon. We compared both the influence of the pre-treatment (carbonization or graphitization) and the influence of the precursor (Rayon or PAN). By thermogravimetric analysis coupled with mass spectrometry (TGA-MS) we showed, that after thermal treatment, the thermal stability was lower for carbonized felts compared to graphitized felts and the Rayon based felts were more stable than PAN based ones. Soaking had a stronger impact on the thermal stability of PAN based felts, whereas it was similar to the electrochemical ageing for Rayon based felts. X-ray photoelectron spectroscopy and Raman spectroscopy revealed that thermal treatment reduces the overall surface oxygen content for all felt types and the degree of graphitization doesn't change, but the content of single bonded oxygen was increased for graphitized carbon felts, only. For carbonized felts, thermal treatment highly reduced the electrochemical activity characterized by cyclic voltammetry due to a reduced overall oxygen content and increased C=O and C=C contents. In this work, we provide a comprehensive overview of commercially available carbon felts and characterize the effects of several treatment methods.